Problems of research on borrowings from the English language - Pak, M.K.; Chekmareva, N.V. (KU Publ., 2021)
This article examines the works of famous linguists, both domestic and foreign, who have studied the problems of the functioning of borrowed vocabulary in the Russian language at different stages of history, starting from the end of the XVII century during the reign of Peter the Great, followed by the period of perestroika at the end of the XX century and ending with modern research and new approaches to solving the problems voiced in our time in the XXI century. We have provided a classification of existing case studies of loan words in the Russian language, which includes periods of time when the research was conducted, the features of the borrowing process, the number of studies on this subject, language-source prevailing at a certain time interval, and the channels where foreign loanwords came from. We identified areas of further study of the problems of foreign languages and loanwords that are common and universal theory of citations as well as being a clear and rigorous classification according to different parameters. Further research on the functioning of the borrowed vocabulary can contribute to the creation of a coherent and practically justified theory of borrowing.
Ағылшын тілінен енген кірме сөздерді зерттеу мəселелері
Проблематика исследований заимствований из английского языка
Keywords: borrowed vocabulary; foreign language vocabulary; historical vocabulary; research directions; relevance of borrowing; foreign language origin; modern research